Percolating cosmic string networks from kination - Conlon, JP; Copeland, EJ; Hardy, E; Sánchez González, N (American Physical Society, 2024)
We describe a new mechanism, whose ingredients are realised in string compactifications, for the formation of cosmic (super)string networks. Oscillating string loops grow when their tension µ decreases with time. If 2H + ˙µ/µ < 0, where H is the Hubble parameter, loops grow faster than the scale factor and an initial population of isolated small loops (for example, produced by nucleation) can grow, percolate and form a network. This condition is satisfied for fundamental strings in the background of a kinating volume modulus rolling towards the asymptotic large volume region of moduli space. Such long kination epochs are motivated in string cosmology by both the electroweak hierarchy problem and the need to solve the overshoot problem. The tension of such a network today is set by the final vacuum; for phenomenologically appealing Large Volume Scenario (LVS) vacua, this would lead to a fundamental string network with Gµ ∼ 10−10.